Multifunctional porous organic polymers embedded with magnetic nanoparticles. Issue 6 (25th January 2017) - Qiao, Shanlin; Huang, Wei; Wang, Ting; Du, Bin; Chen, Xiangning; Hameed, Abdul; Yang, Renqiang
Abstract : Magnetism, a conjugated π-system and ultramicropores are combined in one multifunctional bulk material with a core@shell structure for dynamic and static pollutant treatment. Abstract : Multifunctional hybrid polycarbazoles were prepared with a novel core–spacer–shell structure. Magnetism, a conjugated system and an ultramicroporous structure are combined in one bulk material. SEM and TEM images show the obvious core@shell structure in the nano-region. Nitrogen gas sorption, magnetic and surface wettability analyses indicate the multifunctionality of the obtained materials. Their high efficiency dynamic adsorption (water treatment) and static separation (CH4 /CO2 gas selectivity) allow these novel materials to be employed as facile tools for environmental treatment and in energy storage fields.